2018
DOI: 10.1007/s11325-018-1680-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PAP therapy on hospitalization rates in Medicare beneficiaries with COPD and coexisting OSA

Abstract: Initiation of PAP therapy in elderly patients with overlap syndrome is associated with a reduction in hospitalization for COPD-related conditions, but not for all-cause hospitalizations and ER visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…Singh and colleagues studied a Medicare COPD population with coexisting OSA and reported similar rates of comorbidities (e.g., hypertension, type 2 diabetes, and heart failure) and distribution of COPD complexity (a claims-based proxy for disease severity) to our study ( 36 ). Similarly, the distribution of COPD complexity in the current study is consistent with the Medicare COPD and overlap syndrome populations in the study by Starr and colleagues ( 37 ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Singh and colleagues studied a Medicare COPD population with coexisting OSA and reported similar rates of comorbidities (e.g., hypertension, type 2 diabetes, and heart failure) and distribution of COPD complexity (a claims-based proxy for disease severity) to our study ( 36 ). Similarly, the distribution of COPD complexity in the current study is consistent with the Medicare COPD and overlap syndrome populations in the study by Starr and colleagues ( 37 ).…”
Section: Discussionsupporting
confidence: 73%
“…To our knowledge, there is only one previous study looking at the impact of initiating PAP therapy in an overlap syndrome population. Using a 5% sample of Medicare fee-for-service beneficiaries with COPD, Singh and colleagues identified 319 patients with comorbid OSA ( 36 ). They found that COPD-related hospitalization rates were lower after PAP initiation (identified by Healthcare Common Procedure Coding System codes), but other ER visits and all-cause hospitalization rates did not differ in users versus nonusers of PAP therapy (although the sample size limits the ability to draw definitive conclusions) ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Study Cohort. All patients with COPD were identified as previously reported (9). Exclusion criteria were age 65 years or younger, residence in a nursing facility or enrollment in a health maintenance organization plan, or lack of completed enrollment in Medicare parts A and B for 12 months or longer or until death in Supported by Agency for Healthcare Research and Quality grants R01-HS020642 and R24-HS022134.…”
Section: Methodsmentioning
confidence: 99%
“…Geographic regions were designated by the eight Centers for Medicare and Medicaid Services regions. PSG and PAP therapy were identified as previously described (9).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of medical costs, patients with OVS tend to accrue in one study using a Medicaid database, patients with OVS required on average $4,000 more a year in medical expenditures than patients with COPD alone [10]. Treatment of OSA in those with OVS is associated with improvement in mortality [8] and risk of COPD exacerbation [11], while greater average duration of positive airway pressure (PAP) use shows a dose-response relationship toward outcomes [12]. Thus, aggressive diagnosis and treatment of OSA amongst those with COPD appear to be warranted.…”
Section: Introductionmentioning
confidence: 99%